2007
DOI: 10.1080/03079450701639319
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Marek's disease herpesvirus vaccine virus genome load in feather tips with protection, using an experimental challenge model

Abstract: We previously developed a real-time polymerase chain reaction (PCR) assay for absolute quantitation of serotype 1 Marek's disease virus in feather tips of chickens, and this has been used clinically to monitor a flock's response following vaccination with CVI988, an attenuated serotype 1 strain. The level of vaccine virus in feather tips associated with protection against challenge by virulent virus is not known. Here, we used an experimental challenge model, in which one dose of vaccine gives over 90% protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 31 publications
2
13
0
1
Order By: Relevance
“…Our results indicated that virulence of the challenge MDV did not affect the ability of the vaccine HVT to replicate. It has been proposed that strong replication of MDV vaccine is necessary to acquire adequate protection (3,8,17). Results in this study suggest that adequate replication of HVT is not enough to warrant the protection against challenge with very virulent or very virulent plus challenge.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Our results indicated that virulence of the challenge MDV did not affect the ability of the vaccine HVT to replicate. It has been proposed that strong replication of MDV vaccine is necessary to acquire adequate protection (3,8,17). Results in this study suggest that adequate replication of HVT is not enough to warrant the protection against challenge with very virulent or very virulent plus challenge.…”
mentioning
confidence: 71%
“…Data are presented as the mean and the 0.95 confidence interval. Differences between chickens without lesions (N) and with lesions (Y) at each time point (3,5, and 15 wpc) were statistically studied (Student t-test, P , 0.05). Within each time point, the same letter placed above the bars means that the differences were not significant.…”
mentioning
confidence: 99%
“…The number of copies of the Rispens genome at 21 days post-vaccination is highly variable between birds [93]. Whether quantitation of the genome of vaccinating strains in feathers by qPCR allows to evaluate the level of protection of the flock in poultry farms remains to be determined [93,94]. …”
Section: Excretion Of Vaccinating Strains and Pathogenic Strains mentioning
confidence: 99%
“…The causative agent of MD is MDV, which is ubiquitous, globally distributed and very common in commercial poultry flocks with an estimated cost to the industry more than US$ 1-2 billion (Baigent et al, 2007;Morrow and Fehler 2004). Domestic fowls are the natural host of the MDV, but quail, geese and turkey are also affected.…”
Section: Discussionmentioning
confidence: 99%